NUMBER OF CANDIDA ALBICANS COLONY ON HEAT CURED ACRYLIC RESIN PLATE AFTER IMMERSION IN BASIL LEAF EXTRACT (OCIMUM BASSILICUM LINN ) 50% SOLUTION : JUMLAH KOLONI CANDIDA ALBICANS PADA PLAT RESIN AKRILIK HEAT CURED SETELAH DILAKUKAN PERENDAMAN EKSTRAK DAUN KEMANGI (OCIMUM BASSILICUM LINN) 50% - Kadek Ayu Wirayuni; Sintha Nugrahini (Interdental Jurnal Kedokteran Gigi (IJKG), 2020)
Introduction: Accumulation of plaque and food scraps on an acrylic resin heat cured base will increase bacterial colonies and Candida albicans which will cause denture stomatitis. Maintenance of denture hygiene using mechanical, chemical and combination of two methods. Basil leaf (Ocimum bassilicum Liin) 50% extract contain essential oils which are important to against  Candida albicans biofilms. Purpose: The purpose of this study was to determine the comparison of Candida albicanscolonies after cleaning various denture cleaning methods. Materials and method: The method was an experimental study, and the design was posttest only with control group design. Sample size of heat cured acrylic resin plate is 40x12x3mm. this study use Kruskall-Wallis test and Mann-Whitney test as data analysis for comparison tests between groups (non-parametric test). Result: The results showed that there were significant differences between the various cleansing methods used in reducing Candida albicans colonies. Conclusion: The compotition of flavonoids basil leaf (ocimum Bassilicum Liin) 50% extract is anti-microbial which can prevent the entry of fungi that harm the body.